2016
DOI: 10.3892/ol.2016.5244
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ultrasound-guided thoracentesis catheter drainage for pleural effusion

Abstract: The factors influencing the efficacy of ultrasound-guided thoracentesis catheter drainage were investigated in the present study. A retrospective analysis of clinical data from 435 patients who presented with a pleural effusion was performed. Patients were divided into a control group and an intervention group. Thirty-seven patients in the control group were given standard care using pleural puncture to draw the excess fluid. The 398 patients in the intervention group were treated using ultrasound-guided thora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As respect side of the radiation, the current investigation demonstrated that (half) had left sided pleural emanation and (40%) had right sided pleural emission. while in Kabil ,et al [12] study (56.67%) had right sided pleural emanation and (43.33% %) had left sided pleural radiation.…”
Section: Discussionmentioning
confidence: 82%
“…As respect side of the radiation, the current investigation demonstrated that (half) had left sided pleural emanation and (40%) had right sided pleural emission. while in Kabil ,et al [12] study (56.67%) had right sided pleural emanation and (43.33% %) had left sided pleural radiation.…”
Section: Discussionmentioning
confidence: 82%
“…While CVCs offer numerous benefits, they are not without potential shortcomings. Various types of these catheters may have small side openings that are susceptible to blockages from fibrous bands in the pleura, compromising their effectiveness [ 8 , 20 ]. Operative complications during the drainage process, including bleeding, anastomotic leakage, and chylothorax, can also jeopardize patient safety [ 21 – 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pleural reaction is a common complication of pleural puncture. The incidence rate reported in China is 9.7%-16.8% 5 . The complications of pleural puncture can affects the smooth of operation, and even cause shock, consequently endanger the life of patients.…”
Section: Discussionmentioning
confidence: 99%